Comparison of the cardiovascular risk profile of individuals with obesity and abdominal obesity - Koran, Serhat; Bolatkale, Mustafa; Can, Çağdaş; Acara, Ahmet Çağdaş; Kaptanoğulları Harmankaya, Nazmiye Özlem (Japan International Cultural Exchange Foundation, 2017)
Introduction: Obesity is a worldwide public health problem. In the USA, it is the second leading cause of death after smoking and prevalence is increasing throughout the world. Obesity-related health problems have now become more important than some classic health problems such as malnutrition and infectious diseases. The medical importance of obesity emerges through the close relationship with diseases such as diabetes and coronary artery disease in particular, and other various diseases. Materials and Methods: A total of 177 individuals were included in the study comprising 84 (47.5%) males and 93 (52.5%) females, aged 15- 80 years. The patients were separated into 2 groups of abdominal obesity (n = 94) and obesity (n = 83). Abdominal obesity was defined as waist circumference > 94 cm in males and > 80 cm in females, measured at the level of the umbilicus. For the evaluation of cardiovascular risk profile, lipid profiles (cholesterol LDL, HDL, triglyceride) and inflammatory parameters (CRP and fibrinogen) were examined with early morning 12-hour fasting blood tests. Results: A statistically significant difference was determined between the groups in respect of CRP levels with CRP positivity of 41% in the obese group of 41% and 23.4% in the abdominally obese group. (p < 0.05). The levels of fibrinogen were evaluated as statistically significantly higher in the obesity group than in the abdominal obesity group.(p < 0.05). No statistically significant difference was determined between the groups in respect of HBA1c levels (p > 0.05). Conclusion: The results of the current study showed no statistically significant difference between obese and abdominally obese patients in respect of HBA1c levels and lipid profile but the levels of fibrinogen and CRP were determined to be statistically significantly different. The levels of fibrinogen and CRP in the obese patients were statistically significantly higher than those of the abdominal obesity group (p < 0.05). This indicates a positive correlation between increased BMI and increasing sub-clinical inflammation markers. From the results of this study, abdominal obesity in particular can be assumed as a major risk factor for cardiovascular disease.
Keywords: Abdominal Obesity; Cardiovascular Risk; Obesity